Insemination of dairy goats with estrus induced by the male effect during rainy and dry seasons in Northeastern Brazil (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
This study aimed to evaluate the efficiency of biostimulation (Male Effect) through kidding rate of artificially inseminated goats during rainy (March-April) and dry (August-September) seasons of 2012 at Ceara, Brazil. The male effect was effective regardless of season, resulting in 94.5% of goats in estrus. The pregnancy rate for the dry season (57.6%) was proportionally higher than the rainy season (44.4%). However, the kidding rate has tended (P = 0.074) to be higher in the dry season. In general, the second estrus was more conducive to pregnancy, either to rainy or dry season. Thus, the artificial insemination of goats with estrus induced and synchronized by the male effect can be a feasible management resulting in satisfactory productive and reproductive index.